EXAFS investigation on Sb incorporation effects to electrical transport in SnO2 thin films deposited by sot-gel - Geraldo, V.; Briois, V.; Scalvi, Luis Vicente de Andrade [UNESP]; Santilli, C. V. (Elsevier B.V., 2007)
The effect of Sb doping in SnO2 thin films prepared by the sol-gel dip-coating (SGDC) process is investigated. Electronic and structural properties are evaluated through synchrotron radiation measurements by EXAFS and XANES. These data indicate that antimony is in the oxidation state W, and replaces tin atoms (Sn4+), at a grain surface site. Although the substitution yields net free carrier concentration, the electrical conductivity is increased only slightly, because it is reduced by the high grain boundary scattering. The overall picture leads to a shortening of the grain boundary potential, where oxygen vacancies compensate for oxygen adsorbed species, decreasing the trapped charge at grain boundary. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: EXAFS; tin dioxide films; sol-gel